Research Progress on Long Noncoding RNAs and N6-Methyladenosine in Hepatocellular Carcinoma - Zhang, Wenjie; Wu, Wenlong; Meng, Qiang; Yang, Long; Yuan, Juzheng; Tian, Zelin; Ding, Rui; Zhang, Xuan; Wang, Jianlin; Tao, Kaishan (Frontiers in Oncology, 2022)
N6-methyladenosine (m6A) is an epigenetic modification that widely exists in long noncoding RNAs (lncRNAs) and is involved in the regulation of oncogenes or tumor suppressor genes that form complex enzymes to affect the occurrence of tumors. The abnormal modification of m6A methylation can alter the overall m6A level and thus contribute to the malignant biological behaviors of hepatocellular carcinoma (HCC). LncRNAs related to m6A methylation are involved in lipogenesis, the proliferation, migration and invasion of HCC cells, the stemness of tumor cells and sorafenib resistance. In this review, we systematically elaborated upon the mechanism of network regulation between lncRNAs and m6A methylation modification in the progression of HCC and provided further ideas for exploring the pathogenesis of HCC and identifying new targets for HCC treatment and diagnosis.